Enterprise content management : a business and technical guide - Cameron, Stephen A. (Swindon : BCS, 2011)
Annotation Enterprise Content Management (ECM) tools and strategies enable the capture, management, storage and delivery of an organisation's information, wherever that information exists. The book is essential reading for any executive contemplating or managing their information strategies and any enterprise architect involved in managing the delivery of an ECM solution.
Includes bibliographical references (p. 132-137) and index.
Keywords: Management information systems